Management of acute spontaneous thoracic spinal epidural hematoma causing paraplegia - Fahrudin Alić; Hakija Bečulić; Aldin Jusić; Rasim Skomorac; Mirza Moranjkić; Lejla Hrvat; Lejla Tandir (Medicinski glasnik, 2017)
Aim: To emphasize the importance of early recognition, diagnostic processing and emergent surgical treatment of spontaneous spinal epidural hematoma (SSEH). Methods: A 39-year-old female presented with sudden onset of severe pain between the shoulder blades followed by paraparesis and alerted sensibility in the lower extremities. An hour later she developed paraplegia with sensory deficits below ThIV level, absence of patellar reflex, ankle jerk reflex and sphincter dysfunction. Results: Magnetic resonance imaging (MRI) demonstrated acute extensive epidural mass of thoracic spinal segments (ThI-ThIII). The patient underwent emergent decompressive laminectomy ThI-ThIII with epidural hematoma evacuation within 24 hours of symptoms onset. After the surgical treatment, because of suspicion on spinal arteriovenous malformation, complete diagnostic evaluation with spinal angiography was done and no form of vascular malformation was found. Idiopathic SSEH was diagnosed. Two months later the patient reached complete neurological improvement. Conclusion: The SSEH is a rare condition that should be kept in mind in patients presenting with neurological deficit and a sudden onset of back pain like it was in our case. For early diagnosis, immediate MRI is essential. Prompt surgical decompression such as laminectomy is an absolute surgical indication widely accepted for patients with progressive neurological deficit. The SSEH should be considered as one of the important differential diagnoses in patients who have developed acute myelopathy.
Keywords: neurological impairment; magnetic resonance imaging; decompressive laminectomy